Effective use of social media in public health - Batra, Kavita; Sharma, Manoj (Academic Press, 2023)
Divided into sections, the book addresses the growing use (and importance) of social media in conducting and disseminating research findings and covers an array of issues from cyberbullying to diversity and inclusion.
Includes bibliographical references and index. - Description based on online resource; title from digital title page (ProQuest Ebook Central, viewed May 7, 2024)
Keywords: Social media in medicine; Health services administration -- Data processing; Public health -- Data processing; Medical informatics; Social media; Public Health; Social Media; Medical Informatics; Médias sociaux en médecine; Services de santé; Administration; Informatique; Santé publique; Informatique; Médecine; Informatique; Médias sociaux; public health; social media; Health services administration; Data processing; Public health; Data processing